Analisis Implementasi Kebijakan PT. Jasa Raharja dalam Pemberian Santunan pada Masyarakat yang Mengalami Kecelakaan Diri Tunggal di PT. Jasa Raharja Tk. II Padangsidimpuan - Anjali Marwiyah Siregar; Maidalena Maidalena; Ahmad Muhaisin B Syarbaini (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The inappropriate implementation of PT Jasa Raharja (Persero) compensation for victims of traffic accidents and the disproportionate number of accident victims who receive compensation for their injuries are the basis of this research. The procedure for filing claims on behalf of these victims is still unclear to some people. Therefore, the role of the state should not only be limited to accident prevention efforts, but should also include providing protection to accident victims. The researcher in this study used field research as the research strategy, which was logically examined and organized using a qualitative approach. From June to August, this research was conducted in Batu Nadua Sub-district, Padang Sidempuan City. From the results of this research it is clear that Jasa Raharja and the community have different perspectives on how the policy of providing compensation to victims of traffic accidents should be implemented. According to Jasa Raharja, the policy has been implemented in accordance with the prevailing laws and regulations. However, accident victims see things differently. They argue that Jasa Raharja does not fulfill its obligation to provide fair compensation to every traffic accident victim.